1976
DOI: 10.1161/01.res.38.2.53
|View full text |Cite
|
Sign up to set email alerts
|

The concept of active state in striated muscle.

Abstract: FOR THE purposes of this review, it will be helpful to consider the simple block diagram of a striated muscle system shown in Figure 1. The system has been generalized, in order to be applicable to heart muscle, by including an inotropic state mechanism. The parallel elastic component is necessary to account for resting tension. However, neither of these elements will be discussed further. According to the classical model for muscle contraction proposed by Hill, 1 a contracting muscle can be represented by a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…On the other hand, it is well recognized that muscle shortening accelerates the decay of mechanical activity. 37 " 39 Thus, as shorter muscle lengths are reached, deactivation is accelerated and may represent the basis for the minimum length vs. maximum isotonic lengthening rate relation observed in this and previous studies. 16 -22 If a muscle were completely unloaded at any time during isometric force decline, it would shorten.…”
supporting
confidence: 64%
“…On the other hand, it is well recognized that muscle shortening accelerates the decay of mechanical activity. 37 " 39 Thus, as shorter muscle lengths are reached, deactivation is accelerated and may represent the basis for the minimum length vs. maximum isotonic lengthening rate relation observed in this and previous studies. 16 -22 If a muscle were completely unloaded at any time during isometric force decline, it would shorten.…”
supporting
confidence: 64%
“…3) follows an expected reduction in rate constants (factor per 100C change t 2.5). (iv) The kinetics of the increase in light scattering and tension are slower at low temperatures, as is the variation of myoplasrnic Ca2+ concentration (7,16).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed from studies of isolated cardiac muscle that the maximum velocity of shortening of unloaded muscle (Vma,) on the one hand and the force generated by the cardiac muscle on the other may be dependent upon different mechanisms with different time constants. 18 Indeed, Tyberg et al 19 found, in the isolated papillary muscle contracting isometrically, that the rate of force generated was less sensitive to hypoxia than the actual amount of force generated and proposed that early ischemia might shorten the duration of the active state, while affecting its intensity only slightly. Similarly, in anesthetized animals, hemorrhagic shock depressed cardiac pump performance as reflected by cardiac output and left ventricular diastolic pressure more than it affected V max .…”
Section: Discussionmentioning
confidence: 99%